Lonergan, B.J.F. (1998). For a New Political Economy. Collected Works of Lonergan, Vol. 21. P. McShane (Ed). Toronto: University of Toronto Press. Número de páginas: 336. - Sierra Gutiérrez, Francisco (2014)
null